State control: issues of constitutional and legal regulation - Taitorina, B.A.; Baisalova, G.T.; Assanova, A.A.; Bogatyreva, L.B. (KSU publ., 2020)
The problem of state control does not lose relevance due to a need for compliancy with the foundations of its constitutional system enshrined in the Constitution of the Republic of Kazakhstan. At present, problems arise with identifying potential opportunities and limits of control functions and finding the most effective methods and forms of their implementation. The purpose of this study is to update problems with the constitutional and legal regulations of our Institute of State Control in this modern time. As a result of analysis within the content of the Constitution and a wide range of sources, certain things have been revealed: in the constitution, state control is regulated in a general abstract-systematic form, manifested through the interrelated action of a large number of constitutional norms. The issues of constitutional zing state control are closely related to constitutional and legal policies. The authors associate problems of constitutional and legal regulations within state control with the functioning of the basic law of state and society. As a rule, control functions are a tool, a means of implementing different functions towards the state. The article concludes that control is a statepower activity expressed from control bodies who then must give controlled objects mandatory instructions to eliminate detected deficiencies; initiating the question of bringing to justice those responsible for the revealed violations.
Keywords: law; control; state; constitution; constitutional and legal regulation